2020
DOI: 10.1186/s12893-020-00729-4
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent-level biomechanics after single-level anterior cervical interbody fusion with anchored zero-profile spacer versus cage-plate construct: a finite element study

Abstract: Background: The development of adjacent segment degeneration (ASD) following ACDF is well established. There is no analytical study related to effects of plate profile on the biomechanics of the adjacent-level after ACDF. This study aimed to test the effects of plate profile on the adjacent-level biomechanics after single-level anterior cervical discectomy and fusion (ACDF). Methods: A three-dimensional finite element model (FEM) of an intact C2-T1 segment was built and validated. From this intact model, two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…
Fig. 3 Comparison of finite element analysis results with previous published data [ 24 26 ]. a flexion, b extension, c lateral bending, d axial rotation
…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…
Fig. 3 Comparison of finite element analysis results with previous published data [ 24 26 ]. a flexion, b extension, c lateral bending, d axial rotation
…”
Section: Resultsmentioning
confidence: 84%
“…To reduce the resources required for creating a mesh of the complex spinal geometry, ABAQUS 6.13 (Abaqus Inc., USA) was used to generate a tetrahedral mesh on the vertebrae and a hexahedral mesh on the discs. The material properties were assumed to be homogeneous and isotropic according to the published literature [ 24 29 ]. The annular fibers embedded in the ground substance were assembled in a crisscross manner.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, a zero-profile cage was used in the present ACDF surgery, whereas the biomechanical effect of the zero-profile cage and the cage plus plate on the adjacent segments may be different. Li et al (2020 ) found that the intradiscal pressure of adjacent segments in the plate-interbody model was slightly larger than that in the zero-profile model after single-level ACDF in a FE study. Hua et al ( 2020a ) found that the intradiscal pressure was increased at adjacent segments using either a zero-profile device or cage plus plate while the loss of ROM at the fused segment was larger in cage plus plate group.…”
Section: Discussionmentioning
confidence: 96%
“… Li et al (2021 ) investigated the effect of pre-existing degeneration of adjacent segment on its biomechanics after single-level ACDF. The influences of implant selection on the adjacent-level biomechanics after ACDF were also evaluated in several FE studies ( Li et al, 2020 ; Purushothaman et al, 2020 ; Guo et al, 2021 ; Zhou et al, 2021 ). Hua et al ( 2020a ) and Hua et al (2020b ) compared the biomechanical changes of adjacent segments after one- or two-level anterior cervical surgery with different implants.…”
Section: Introductionmentioning
confidence: 99%
“…The material properties of the finite element model were given in Table 1. 2024 After the convergence test was conducted, we found 0.5 mm is optimum size for the element. 25 The percentage of accuracy of the convergence test is 3% for the finite element model.…”
Section: Methodsmentioning
confidence: 96%